2011
DOI: 10.1155/2011/941872
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of a Forward Swept Rotor in a Multistage Fan with Inlet Distortion

Abstract: Previous studies of transonic swept rotors in single stage fans have demonstrated the potential of significant improvements in both efficiency and stall margin with forward swept blading. This paper extends the assessment of the payoff derived from forward sweep to multistage configurations. The experimental investigation compare two builds of an advanced two-stage fan configuration tested alternately with a radial and a forward swept stage 1 blade. In the two-stage evaluations, the testing was extended to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The flow field analysis showed that the positive curved stator improved the flow field in the distortion region, but it increased the friction loss in the non-distorted region due to the increase of curved blade surface area. Wadia et al 17 reported that the forward swept rotor presented a superior aerodynamic performance and tolerance to the non-uniform inflow.…”
Section: Introductionmentioning
confidence: 99%
“…The flow field analysis showed that the positive curved stator improved the flow field in the distortion region, but it increased the friction loss in the non-distorted region due to the increase of curved blade surface area. Wadia et al 17 reported that the forward swept rotor presented a superior aerodynamic performance and tolerance to the non-uniform inflow.…”
Section: Introductionmentioning
confidence: 99%
“…Also, inflow distortion exacerbates the high cycle fatigue of the blade in the compressor (Engeda et al, 2003;Zemp et al, 2010). Wadia (2011) conducted a pilot of the performance of a forward-swept rotor in a multi-stage compressor under inflow distortion and found that the inlet guide vane row reduced the sensitivity of the multi-stage compressor to inflow distortion; moreover, it augmented the vibration amplitude of the blade. Gunn et al (2013) developed full-annulus experimental measurements of the flow field in a low-speed fan stage operating with a continuous 60-degree inlet stagnation pressure distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Passive control of inlet distortion can be implemented with casing treatment (Prince et al, 1975;Smith and Cumpsty, 1984) or blade modification (Wadia et al, 2002). Active control methods for inlet distortion include tip injection, bleeding of flow and the application of variable inlet guide vane (VIGV) (Wadia, 2011). Both tip injection and bleeding can improve the stall margin with inlet distortion when stall is initiated at the tip, though bleeding is relatively less effective as compared with injection (Koch, 1970).…”
Section: Introductionmentioning
confidence: 99%